2008
DOI: 10.1142/s1793604708000307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nickel Niobate B-Site Precursors on Phase Formation, Microstructure and Dielectric Properties of Perovskite PNN Ceramics

Abstract: Relaxor perovskite lead nickel niobate (PNN) ceramics were fabricated by using B-site precursor method, in which both columbite-NiNb 2 O 6 and corundum-Ni 4 Nb 2 O 9 were separately employed as nickel niobate B-site precursors. It has been found that optimization of sintering condition can successfully lead to highly dense and pure PNN ceramics in both routes. Between the two B-site precursor routes, pure perovskite PNN ceramics with slightly better densification and dielectric properties can be produced by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…34-374 earlier reported by Srisombat et al [4] was found to co-exist along with perovskite PZN. This may be attributed to the loss of PbO after sintered at 1050 • C for prolong dwell time of 5 h, which is commonly found in other Pb-based perovskite systems [3,5]. On the other hand, a single phase of perovskite PZN was found in both the PZN-Z and PZN-ZB routes.…”
Section: Methodsmentioning
confidence: 86%
“…34-374 earlier reported by Srisombat et al [4] was found to co-exist along with perovskite PZN. This may be attributed to the loss of PbO after sintered at 1050 • C for prolong dwell time of 5 h, which is commonly found in other Pb-based perovskite systems [3,5]. On the other hand, a single phase of perovskite PZN was found in both the PZN-Z and PZN-ZB routes.…”
Section: Methodsmentioning
confidence: 86%